2017
DOI: 10.1016/j.cgh.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the Guaiac Fecal Occult Blood Test With the Fecal Immunochemical Test Increases Proportion of Individuals Screened in a Large Healthcare Setting

Abstract: In a retrospective study of patients at a Veterans' administration healthcare system, replacing the gFOBT with the FIT increased the proportion of patients who completed CRC screening. Replacement of the gFOBT with the FIT should be strongly considered by all healthcare systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
1
32
0
5
Order By: Relevance
“…This rate is similar to that determined from a large database of Veteran's Affairs data in the US (42.6%). [46] Based on meta-analysis data, annual HSgFOBT is ~16% [29] to 21% [38] relatively lower than FIT, thus, HSgFOBT adherence rates of 16% lower relative to FIT were assumed.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is similar to that determined from a large database of Veteran's Affairs data in the US (42.6%). [46] Based on meta-analysis data, annual HSgFOBT is ~16% [29] to 21% [38] relatively lower than FIT, thus, HSgFOBT adherence rates of 16% lower relative to FIT were assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a probabilistic sensitivity analysis will also help demonstrate variation of estimated outcomes due to uncertainty in model input parameters. Finally, data on studies that have reported on adherence rates are limited and can vary across different populations, healthcare systems, and geographies . Given these caveats, we performed several sensitivity analyses and provided information on the clinical outcomes for each screening modality at different adherence rates.…”
Section: Discussionmentioning
confidence: 99%
“…One‐time adherence to colonoscopy was estimated at 38% . The one‐time adherence rates for FIT and HS‐gFOBT were modeled at 42.6% and 33.4%, respectively, based on an observational study of 7898 patients who were offered stool‐based CRC screening . We assumed that the adherence rate of FIT‐DNA was similar to that of FIT.…”
Section: Methodsmentioning
confidence: 99%
“…Although non-invasive screening tests provide options to individuals who do not want to be screened by more invasive methods, the efficacy of these tests is largely dependent upon consistently completing them when required. Relatively poor test completion rates are one reason why HSgFOBT has been suggested to be replaced by FIT in particular US settings where HSgFOBT is still used [38]. As demonstrated in this report, harm-benefit tradeoffs and optimal test selection directly depend upon particular adherence patterns.…”
Section: Discussionmentioning
confidence: 87%